Meteorological and Hydrological Disasters Bangladesh Experiences Every Year Monitored Through Space Technology - Begum, Suraiya; Alam, Md Shah; Nessa, Mehrun; Ali, Md Shajahan; Molla, Md Firoz (Journal of Future Internet, 2014)
The physical cause of this disaster is embodied in law of science and hence proper scientific research is necessary to deal with them. Bangladesh is one of the disaster prone country faces Cyclones, Floods, draught, Norwesters/Tornadoes, Earthquake etc. almost every year. The Role of Remote Sensing in the monitoring such natural disasters has been described in this paper.